Enhancing green loyalty towards apparel retail stores: A cross-generational analysis on an emerging market - Dan Cristian Dabija (Journal of Open Innovation: Technology, Market, and Complexity, 2018)
Faced with an array of scandals and challenges caused by environmental pollution and exploitation of workers, apparel retailers are often compelled to re-think their strategies in compliance with environmental governance, and to implement specific measures aimed at environmental protection and preserving resources. By adopting green-based strategies to reach their target segments, retailers seek not only to capture the attention of different consumer generations, but also to inspire loyalty and encourage them to re-visit stores. Based on the generational theory and by means of quantitative research addressing four consumer generations in an emerging market, the authors highlight the extent to which clothing retailers are able, by adopting green strategies and consistently implementing environmental protection actions, to attract mainly young consumers to their stores, encouraging the sharing of peer recommendations, increasing purchasing behaviour and invoking loyalty. The article highlights the contribution of green marketing strategies in developing consumer loyalty in an emerging market by offering retailers the possibility of deepening their understanding when approaching different consumer generations.
Keywords: 650; Consumer generations; Cross-generational analysis; Apparel retail; Emerging market; Green-oriented retail stores; Consumer loyalty